PENGARUH PERSEPSI POLITIK ORGANISASIONAL TERHADAP KEPUASAN KERJA YANG DIMODERASI KETRAMPILAN POLITIK - Fauziah Jahra Cintana; Nang Among Budiadi; Sugiyarmasto . (Jurnal Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to examine the effect of organizational political perceptions on job satisfaction moderated by political skills. This research is important because it is able to examine the significance of the relationship between organizational political perceptions and political skills on job satisfaction. This research uses survey research methods through questionnaires. The object of research is all hospital employees in the city of Surakarta with a sample of 159 respondents. Sampling in this study using the probability sampling method. The analytical tool used in this study is simple linear regression while the moderating analysis tool uses regression analysis tools. The results showed H1 had a significant relationship while H2 did not have a significant relationship. These results give the sense that organizational political perceptions affect job satisfaction. While political skills as a moderator between organizational political perceptions do not affect job satisfaction.